Chemotherapy-Induced Cardiotoxicity: Comprehensive Review of Mechanisms, Diagnosis, and Management - Mohammed Jamal Ahmed; Abdulrahman Ahmed Mahmood; Ali Mohammed Salih; Daban Noori Hama Saeed; Akam Dler Latif; Klaudia Chuchracka; Rebaz Ramadhan Abdulrahman (Asian Journal of Pharmaceutical Research and Development, 2025)
Background: Chemotherapy-induced cardiotoxicity is a perilous consequence that limits the use of potent anticancer medicines, especially anthracyclines. Notwithstanding progress in oncology, cardiovascular toxicity continues to be a significant contributor to morbidity and mortality among cancer survivors. Objective: This review examines the molecular mechanisms, diagnostic approaches, and management strategies for chemotherapy-induced cardiotoxicity, emphasizing the need for early detection and interdisciplinary collaboration between cardiologists and oncologists. Key Findings: Cardiotoxicity manifests as left ventricular dysfunction (LVD), arrhythmias, or heart failure (HF), with anthracyclines and trastuzumab being the most implicated agents. Advanced imaging (e.g., strain echocardiography, cardiac MRI) and biomarkers (troponin, NT-proBNP) enable early detection before irreversible damage occurs. Dexrazoxane, ACE inhibitors, and beta-blockers show promise in prevention and treatment, though optimal protocols remain under investigation. Conclusion: Proactive monitoring and personalized cardioprotective strategies are essential to balance oncological efficacy with cardiovascular safety. The following studies require concentrating on extensive trials to enhance risk classification and therapy strategies.